Development of the method for the formation of one-dimensional contours by the assigned interpolation accuracy - Havrylenko, Ye.; Kholodniak, Yu.; Vershkov, O.; Naidysh, A. (My University, 2018)
EN: Geometric modeling is one of the tools for investigation of objects, phenomena and processes. The task of geometric modeling is to determine properties of an object being modeled using characteristics of a geometric model. Output data are geometric images assigned by a set of points. Their location reflects properties of the examined object. Geometric characteristics of a discretely represented geometric image (line or surface) can be given at the output points. We can obtain output by calculations or measurements at physical objects. UA: Запропоновано метод формування одновимірних обводів виходячи з заданої точності інтерполяції. Максимальна абсолютна похибка інтерполяції визначається з урахуванням геометричних властивостей вихідної кривої лінії. Розглядається два різновиди похибки. По-перше, похибка, з якою сформована дискретно представлена крива, що інтерполює вихідний точковий ряд, представляє вихідну криву. По-друге, похибка, з якою інтерполююча крива представляє будь-яку криву з заданими геометричними характеристиками. RU: Предлагается метод формирования одномерных обводов исходя из заданной точности интерполяции. Максимальная абсолютная погрешность интерполяции определяется с учетом геометрических свойств исходной кривой линии. Рассматривается две разновидности погрешности. Во-первых, погрешность, с которой сформированная дискретно представленная кривая, интерполирующая исходный точечный ряд, представляет исходную кривую. Во-вторых,погрешность, с которой интерполирующая кривая представляет любую кривую с заданными геометрическими характеристиками.
Keywords: processes; model; geometric image; curve; surfaces; one-dimensional contours; похибка інтерполяції; упорядкована множина точок; осциляція; монотонна зміна диференціально-геометричних характеристик; погрешность интерполяции; упорядоченное множество точек; осцилляция; монотонное изменение дифференциально-геометрических характеристик